Efektivitas amoxycillin terhadap streptoÂcoccus sp. yang ditularkan pada ikan karper (cyprinus carpio L)= Effectiveness of Amoxycillin againts the Streptococcus sp. Infected to Karper Fish (Cyprinus Carpio L) - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
This research was done to determine the effectiveness of amoxycillin against the streptococcus sp. infected to karper fish (Cyprinus carpio L) which was held at Wet Laboratorium Fish Quarantine Station Selaparang Mataram. Pre-test was done to know the sensitiveness of several kinds of antibiotics, such as : amoxycillin, cyprofloxacin, contrimoxazole and doxycycline. The result of in vitro test showed that the value of minimum inhibitory concentration (MIC), the lowest at amoxycillin (10 ppm), with the value of minimum bactericidal concentration (MBC) was 15 ppm. Based on MBC test, amoxycillin was used as test medicine with dosage 15 ppm. For getting infection dosage of Streptococcus sp, against karper fish, the LC-50 test was applied. Based on this test, it was found that the bacterial concentration of 4.6612 x 1014 cell/ml was as infectious dosage. Superior test was done with 8 phases which were divided into 2 groups, i.e. the cure and prevention tests. Each test was done with 5 phases including control with 3 replication times. Each phase was used with aquarium which was put 15 karper fish with 30 1 water volume. Amoxycillin dosage used in the cure and prevention tests was 15, 30, 45 and 60 ppm. The clinical signs and phatological lesions seen during the present study were dark/pale skin color, very slow swimming, lordosis and scoliosis, opened/folding operculum, big belly and exophthalmic eyes. After doing the cure and prevention tests, as a matter of fact the degree of survival was raised 24.45 % compared to the control. According to the result of statistical analysis, there was no any significant differences between phases. The result of inspection towards karper fish which was still sick during the research on cure dosage showed the significant differences. At the control, the karper fish was still sick 100 % and D (60 ppm) 0%. The calculation of analyze of kind investigation and test double distance of Duncan, phase aquarium A showed the real difference with phase aquarium B, C and D, but between phase aquarium B, C and D had no significant differences. There was also no significant differences between phases at superior test of prevention dosage. Based on the result of research it was concluded that amoxycillin 30 ppm gave effective results for curing karper fish that was infected by Streptococcus sp.